Journal of Finance and Investment Analysis 2021
DOI: 10.47260/jfia/1012
|View full text |Cite
|
Sign up to set email alerts
|

Financial Engineering and Financial Performance of Deposit Taking Savings and Credit Co-operative Societies in Kenya.

Abstract: The study explores the effect of financial engineering on financial performance of deposit taking Savings and Credit Co-operative Societies (SACCOs) in Kenya. Population constituted of 163 SACCOs and a sample of 45 was considered. The results depicted that SACCOs have adopted financial engineering practices in three forms: product engineering, process engineering and financial solutions engineering. In terms of their effect on performance, only process engineering was found to have a positive and significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The examination's conclusion demonstrated that artificial intelligence technologies had a favorable impact on efficient audit procedures, which raised the financial quality of the financial reports that the auditors certified. The potential effects of applying financial engineering to the financial performance of certain deposit banks that fall under the categories of savings and credit cooperative financial institutions were also examined by Kiprotich and Onsomu (2021).The study employed structured questionnaires and survey-based field research methods. Workers at 163 cooperative financial institutions in Kenya, of which 45 institutions made up the study's sample size, made up the population of the research.…”
Section: Artificial Intelligence and Financial Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…The examination's conclusion demonstrated that artificial intelligence technologies had a favorable impact on efficient audit procedures, which raised the financial quality of the financial reports that the auditors certified. The potential effects of applying financial engineering to the financial performance of certain deposit banks that fall under the categories of savings and credit cooperative financial institutions were also examined by Kiprotich and Onsomu (2021).The study employed structured questionnaires and survey-based field research methods. Workers at 163 cooperative financial institutions in Kenya, of which 45 institutions made up the study's sample size, made up the population of the research.…”
Section: Artificial Intelligence and Financial Engineeringmentioning
confidence: 99%
“…The study used the employed the following regression model consisted with the study of Kiprotich and Onsomu (2021).…”
Section: Model Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the report also highlighted that the return on assets (ROA) of SACCOs decreased from 2.7% in 2020 to 1.6% in 2021, indicating a decline in financial performance (SASRA, 2021). Kiarie et al (2019) examined the relationship between expansion decisions and the financial performance of SACCOs in Kenya. The study found that expansion decisions significantly affect the financial performance of SACCOs, but the relationship is complex and varies based on factors such as size, membership, and market conditions.…”
Section: Statement Of the Problemmentioning
confidence: 99%